Given:
Center ==> (4, 1)
Length = 8
c = 3
Let's find the equation for the given ellipse that statisfies the conditions above.
Take the equation:
![((x-x1)^2)/(a^2)+((y-y1)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/so14jll94ut4fo5n5wp1s7h1yg7cb9g6ff.png)
Here, we have a vertical minor axis with points: (x, y) ==> (4, 1) which has the equation below:
Substitute 4 for x1 and substitute 1 for y1
![((x-4)^2)/(a^2)+((y-1)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/a92q95ygb6928ucxfalhlof5pq0vgw9sml.png)
Where:
![c^2=a^2+b^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/udh1dsx7kwgfauditnn86pp2qhoycm1tvv.png)
Since the minor axis is vertical and has a length of 8, we have:
![\begin{gathered} 2b=8 \\ \\ \text{Divide both sides by 2:} \\ (2b)/(2)=(8)/(2) \\ \\ b=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jo14rdq5turiud29jlc2wcz4u9c5mzzbru.png)
Given: c = 3
To find the value of a, substitute 3 for c and 4 for b:
![\begin{gathered} c^2=a^2+b^2^{} \\ \\ 3^2=a^2-4^2 \\ \\ \text{Add 4}^2\text{ to both sides:} \\ 3^2+4^2=a^2-4^2+4^2 \\ \\ 3^2+4^2=a^2 \\ \\ \text{Take the square root of both sides:} \\ \sqrt[]{3^2+4^2}=\sqrt[]{a^2} \\ \\ \sqrt[]{3^2+4^2}=a \\ \\ \sqrt[]{9+16}=a \\ \\ \sqrt[]{25}=a \\ \\ 5=a \\ \\ a=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hg3vlfvwxjoldskk4nasp4wq45atqwy5n1.png)
Therefore, from the general equation, substitute 5 for a, and 4 for b
![\begin{gathered} ((x-4)^2)/(a^2)+((y-1)^2)/(b^2)=1 \\ \\ \\ ((x-4)^2)/(5^2)+((y-1)^2)/(4^2)=1 \\ \\ \frac{(x-4)^2}{25^{}}+\frac{(y-1)^2}{16^{}}=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qiessuqumghjz8gx59psotyu4lxw02gc75.png)
Therefore, the equation for thr given ellipse that satisfies the given conditions is:
![\frac{(x-4)^2}{25^{}}+\frac{(y-1)^2}{16^{}}=1](https://img.qammunity.org/2023/formulas/mathematics/college/fcgt6crz650ldi2g6p5wq2y4y4xsenow6i.png)
ANSWER:
![\frac{(x-4)^2}{25^{}}+\frac{(y-1)^2}{16^{}}=1](https://img.qammunity.org/2023/formulas/mathematics/college/fcgt6crz650ldi2g6p5wq2y4y4xsenow6i.png)